Genetic improvement of cattle and buffaloes in smallholder production systems in India - TRIVEDI, K R; NAYEE, N G; SAHA, S; GAJJAR, S G; KISHORE, G; NAMJOSHI, M; SUDHAKAR, A; GUPTA, R O (The Indian Journal of Animal Sciences, 2021)
Cattle and buffaloes have been supporting livelihoods of a large number of poor farmers in India. Eighty-five percent of 63 million dairy households are smallholder having less than three animals. The country has 191 million cattle and 105 million buffaloes and 37 distinct cattle and 13 buffalo breeds. During 2017–18, the country produced 115 million semen doses and carried out 100 million inseminations, but efforts towards genetic improvement were negligible prior to the launching of National Dairy Plan (NDP) by National Dairy Development Board in 2012. Under NDP, 13 progeny testing (PT) and 10 two-tier nucleus schemes (referred to as Pedigree Selection (PS)) have been initiated. This paper describes the experiences of implementing these programs. During the period between 2012 and 2018, the PT programs together have completed test mating of about 2,000 bulls and built the infrastructure to test annually more than 400 bulls and evaluate them for various traits with 70–100 daughter records per bull. Breeding values are estimated every six months. The PT and PS programs together have supplied 1,720 young bulls, replacing about 40% of the AI bulls in the country. The key learning of implementing PT and PS includes: implementing a classical PT program is not feasible under Indian conditions; producing young males using progeny tested semen and selecting them based on their breeding value is feasible; introduction of genomic selection is very relevant; unravelling environmental effects from genetics under the smallholder production system is the key challenge; developing an appropriate information system is the key to success; evolving right institutional arrangement is very important, and genetic improvement has to be treated as a public good and programs need to be publicly funded at least for the initial 15 years.